Pre-Emptive Analgesic Effect of Intravenous Paracetamol in Modified radical mastectomy - Wagle, Bhawana; Regmi, Yogesh; Shrestha, Sudhir; Thapa, Pradeep; VishowKarma, Suraj; Mandal, Meg Raj; Kandel, Sujan; Singh, Sumit; Mauni, Deepak; Khanal, Durga (Nepalese Journal of Cancer, 2018)
Background: Modified radical mastectomy (MRM) is associated with significant post-operative pain. Intravenous (iv) paracetamol provides pain relief in most patients who have undergone MRM. It has been observed from previous studies conducted on patients undergoing other surgeries like abdominal surgeries that the analgesic efficacy of iv paracetamol improves when used Pre-emptively. There are no studies done previously on use of iv paracetamol Pre-emptively in MRM. Objective: The purpose of the study was to determine the post-operative analgesic effects of Pre-emptive intravenous (iv) paracetamol in MRM. Materials and Methods: Following institutional ethics committee approval, fourty American Society of Anesthesiology (ASA) physical status I-II patients were assigned in a randomized manner into two groups: Group I received iv paracetamol 1g, in 100mL, 15 minutes before induction and Group II received iv paracetamol 1g, in 100 mL, at the end of the surgery. The time to first analgesic use and the total analgesic consumed in 24 hours was recorded. Visual Analog Scale (VAS) pain scores were obtained from all patients at 0, 30 minutes, 1, 2, 6, 12 and 24 hours after the end of the Surgery. Results: Time to first analgesic requirement was significantly longer in Group I compared to Group II (p = 0.0329). Rescue analgesic consumption and post-operative VAS pain scores recorded were significantly lower in Group I compared to Group II (p < 0.05) until 24 after surgery. Conclusion: Pre-emptive iv paracetamol in comparison to intra- operative paracetamol, provided effective and reliable post- operative analgesia after modified radical mastectomy.